Navigating the Future of Healthcare: What is the Approval Process for Medical AI? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI and Machine Learning ML into medical devices and clinical decision support systems is transforming healthcare, ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation